Reactualization of Islamic Values in Supporting the National Sustainable Development Agenda - Inayah; Moh Ali; Taqiyuddin; Ade Hidayah (JURNAL ILMIAH GEMA PERENCANA, 2026)
This study examines the reactualization of Islamic values in supporting Indonesia's national sustainable development agenda, particularly within the framework of the Sustainable Development Goals (SDGs). The background of this research departs from the observation that Indonesia, as the world's largest Muslim-majority nation, has yet to fully integrate Islamic ethical principles such as Maqasid al-Shariah, zakat, waqf, and social justice into its formal national development planning. A normative-qualitative approach based on library research was employed, utilizing primary and secondary sources analyzed through philosophical and thematic analysis. The findings reveal that Islamic values are substantially aligned with the SDGs in areas such as poverty alleviation, quality education, environmental stewardship, and social equity. The five objectives of Maqasid al-Shariah (protection of faith, life, intellect, posterity, and property) correspond directly to multiple SDG targets. Additionally, Islamic philanthropic instruments such as zakat and waqf have demonstrated measurable contributions to poverty reduction and social welfare in Indonesia. This study recommends that national planners formally integrate Islamic value frameworks into policy instruments, including through the optimization of BAZNAS, the Badan Wakaf Indonesia, and Islamic social finance ecosystems. The study contributes to the growing body of literature linking religious ethics to sustainable development planning, and argues that reactualization rather than marginalization of Islamic values represents a strategic asset for achieving Indonesia's 2030 development commitments.